Radiative Cooling Potential of a Water-Based Paint Formulation under Realistic Application Conditions - Lio, Giuseppe Emanuele; Werlé, Jérémy; Arduini, Mariacarla; Wiersma, Diederik Sybolt; Manara, Jochen; Pattelli, Lorenzo (ACS applied optical materials, 2024)
Passive radiative cooling (PRC) technology holds promise to offset a significant fraction of our energy needs and carbon footprint associated with cooling. Among different approaches, paint-like systems present several advantages in terms of cost effectiveness, scalability, and application ease. However, most of the recent paint formulations capable of daytime PRC rely on the use of organic solvents which increase their cost, environmental impact, and safety hazards. Lightweight, water-based formulations are particularly desirable to suppress the emission of volatile organic compounds (VOCs) altogether and expand their applicability. We report on a simple paint mixture, with a solar reflectance of 90% and a thermal emissivity of 95%, comprising a mixture of glass bubbles and PVDF-HFP used directly in its powder form. The paint is tested under conditions relevant for its application in the building sector without sealing it from convection. Depending on the choice of the ambient temperature reference, a material with this degree of solar reflectance is found to exert either vanishing daytime cooling power or up to 100 W m–2, highlighting the importance of rigorous testing and explaining the large performance variations found in the literature for PRC materials with similar spectral properties.